One way ticket : - Bassett, Jennifer (Oxford Univ. Press, 1998)
Tom Walsh had a lot to learn about life. He liked traveling, and he was in no hurry. He liked meeting people, anyone and everyone. This is a collection of short stories about adventures on train. As the wheels of the train turn, these stories show us three different journeys, three different people - all locked in the closed world of the train... where anything can happen